Intracranial Rosai-Dorfman Disease: pathophysiology, diagnosis and treatment - Szymoniuk, Michał; Dryla, Aleksandra; Pytka, Michalina; Kamieniak, Piotr (Journal of Education, Health and Sport, 2022)
Introduction and purpose: ​Rosai-Dorfman Disease (RDD), known also as sinus histiocytosis with massive lymphadenopathy(SHML) is a benign histiocytic proliferative syndrome. The etiology and pathogenesis of RDD remains unclear. Central nervous system involvement is a rare event and concerns approximately 7.8% of RDD cases, whereas intracranial lesions constitute almost 90% of CNS-RDD cases. The aim of this literature review was to summarize current knowledge about the diagnosis and treatment of intracranial manifestation of RDD. We also described possible hypotheses regarding the pathophysiology of this disorder. State of knowledge: ​Even though Rosai-Dorfman disease was thought to be a reactive process, recent evidencedemonstrate the presence of clonality, which means that in this histiocytosis the process that underlies the pathology is neoplastic. Intracranial lesions caused by RDD can be easily misdiagnosed with many diseases such as meningiomas, malignant gliomas or metastatic tumors. The final diagnosis of Rosai-Dorfman disease should be made based on histologic and immunohistochemical examinations. Current therapeutic options for this condition include surgery, radiotherapy, chemotherapy, corticosteroids and immunotherapy. Surgical treatment often constitutes the first-line treatment for intracranial RDD and is the most beneficial treatment option. However, the implementation of adjuvant therapies is very important to avoid the recurrence of lesions, which appear in approximately 14% of subjects after about 10 years from surgery. Conclusion: ​This literature review presents current data about pathophysiology, diagnosis and treatment of intracranial involvement of Rosai-Dorfman disease. Further studies on this topic should focus on exploring etiologic mechanisms underlying on this pathology and comparing available treatment methods.